Linda X and Kim X interviewed by Loretta Ribaudo in the Cultural context of unemployment oral history project - X., Linda; Ribaudo, Loretta; X, Kim, 1963?-; Cultural Context of Unemployment Project. Perth Team. (1985)
Linda and Kim who are currently employed, speak of their work experience ; leaving school and subsequent lifestyles for the first few years ; lifestyle now ; current employment ; changes since finding work ; CEP projects ; unemployment ; doing charity work ; family ; young unemployed ; CES ; looking for work ; Dept. of Social Security ; community and government attitudes to unemployment ; feelings and emotions caused by unemployment ; lack of self esteem of the unemployed ; working for the dole ; need for help for over 25's who are unemployed ; crime and the unemployed ; feeling desperate ; drugs and the unemployed ; the government and what should be done to help the unemployed.
Recorded by the Perth Team (School leavers) of the Cultural Context of Unemployment Project, a CEP Program administered by the National Library of Australia.
Digital master available
Transcript available (40 p.)
Keywords: X., Linda -- Interviews; X., Kim, -- 1963?- -- Interviews; Unemployment -- Social aspects -- Western Australia -- Perth; Women -- Employment -- Western Australia -- Perth